Interventions to support the mental health of family carers of children with brain injury in low and middle income countries: a scoping review - M. A. Linden; R. Leonard; L. Ewing-Cobbs; K. C. Davis; L. Schrieff-Brown (Frontiers Media S.A., 2024)
AimTo review the international evidence base on interventions to support the mental health of family carers of children with brain injuries in low and middle income countries (LMIC).MethodsSearches were conducted with five electronic databases (Pubmed, Web of Science, Embase, PsycINFO, CINAHL) using search terms related to "family carers", "brain injury", "children" and "low and middle income countries". Studies were independently screened using predetermined eligibility criteria by two authors. Data were extracted from included studies using standardised data extraction and quality appraisal tools. These data were then subjected to narrative synthesis. The Preferred Reporting Items for Systematic reviews and Meta-Analyses (PRISMA) guidelines were used to govern the review process.FindingsOne study met our inclusion criteria and described an acquired brain injury called nodding syndrome which occurs in Sub-Saharan Africa. The study was conducted in Ghana and provided group-based psychotherapy to carers and their children. As such we found no study which sought to solely support the mental health of family carers.ConclusionsThere has been a lack of focus in the literature on the mental health of family carers of children with brain injuries in LMIC. Considering the vital importance of caregivers in supporting their children it is imperative that service providers and researchers devise programmes to better meet their needs. The mental health of family carers should be better supported to improve their overall wellbeing, which will in turn improve the wellbeing of their children.